Percutaneous balloon dilatation of aortic valve stenosis in neonates and infants. Issue 6 (December 1987) - Wren, C; Sullivan, I; Bull, C; Deanfield, J
Abstract : Percutaneous balloon dilatation of severe aortic valve stenosis was attempted in thirteen patients (seven neonates and six infants). In two the valve could not be crossed and both died during subsequent operation. Two patients died during manipulation of the balloon catheter. No significant benefit was obtained in another patient who later died during operation. Balloon dilatation was successful in the remaining eight patients, reducing the aortic valve pressure gradient from a mean of 63 mmHg (95% confidence interval 38 to 88 mmHg) to a mean of 23 mmHg (95% confidence interval 7 to 39 mmHg). Two of these patients subsequently died from heart failure related to other cardiac lesions. The six survivors have done well. At follow up the maximum Doppler velocities in the ascending aorta ranged from 1.9 to 4.0 m/s after 2-23 months, but despite this evidence of an increasing valve gradient there has been lasting clinical improvement.